Analisis Kaitan Angka Beban Ketergantungan dengan Indeks Pembangunan Manusia dalam Pemanfaatan Bonus Demografi (Studi 6 Provinsi Indonesia) - Suparna Parwodiwiyono; Witono Witono (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2022)
The dependency ratio (DR) is an indicator of the demographic bonus. This paper aims to obtain of the development and relationship of demographic bonus with human development in 6 selected provinces. The six selected provinces, namely DKI Jakarta and Yogyakarta Special Region, represented low DR members. Sumatra Selatan and Bengkulu represent medium DR. Sulawesi Tenggara and Nusa Tenggara Timur represent high DR members. This study uses secondary data from the publications of the Statistics Indonesia. Data analysis is descriptive quantitative. There are differences in the development of DR in the three categories of areas. Regions with low DR tend to increase, while regions with high DR tend to decline in the 2010-2040 period. Regions with lower DR have a high value of the human development index (HDI), while regions with higher DR have a relatively low HDI value. The demographic bonus is optimized through quality improvement in the fields of education, health, and economy. Policies that are focused and can support of the demographic bonus require special attention from local governments. In addition, it is necessary to support population policies in controlling quantity, developing quality, and directing mobility.